2008
DOI: 10.1590/1809-9823.2008.11029
|View full text |Cite
|
Sign up to set email alerts
|

A atenção à saúde do idoso: ações e perspectivas dos profissionais

Abstract: RESUMO O crescente aumento da população idosa e os complexos problemas de saúde que a envolvem tornam evidente a necessidade de atenção adequada à sua saúde, e espera-se que a Estratégia de Saúde da Família (ESF) possa trazer contribuições. O presente estudo propõe-se a analisar a percepção de profissionais que atuam na ESF quanto à saúde do idoso, as ações que vêm sendo desenvolvidas e as perspectivas dos profissionais visando à promoção, prevenção, cura e reabilitação das condições de saúde deles. Trata-se d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
16

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 14 publications
0
13
0
16
Order By: Relevance
“…22 Estudo realizado com profissionais atuantes na Atenção Primária em Saúde, objetivando analisar a percepção dos mesmos quanto à saúde do idoso, demonstra que a atenção a essa faixa etária é complexa e deve ser pautada na integralidade; sobretudo, é necessário que haja constante investimento na capacitação dos profissionais, além de atenção baseada na visão multidimensional e interdisciplinar do idoso. 23 O mesmo se pensa no panorama das ILPIs, como alternativa para suprir as carências dos profissionais, no que se refere a implementar um plano de ação compatível com as necessidades dos institucionalizados.…”
Section: Mais Horas Para O Trabalho Em Ilpis Diante Da Dificuldade Emunclassified
“…22 Estudo realizado com profissionais atuantes na Atenção Primária em Saúde, objetivando analisar a percepção dos mesmos quanto à saúde do idoso, demonstra que a atenção a essa faixa etária é complexa e deve ser pautada na integralidade; sobretudo, é necessário que haja constante investimento na capacitação dos profissionais, além de atenção baseada na visão multidimensional e interdisciplinar do idoso. 23 O mesmo se pensa no panorama das ILPIs, como alternativa para suprir as carências dos profissionais, no que se refere a implementar um plano de ação compatível com as necessidades dos institucionalizados.…”
Section: Mais Horas Para O Trabalho Em Ilpis Diante Da Dificuldade Emunclassified
“…14 The lack of preventive and promotional health by professionals slips into a curative attention yet, limiting the possibility of a qualified hearing, bond and accountability, which are essential for an effective practice of adherence to therapy. 13 Other authors 14 corroborate the above model and point-dressing emergency as unable to produce personalized attention and create bond with the patient so that it can feel safe and motivated to adhere to treatment.…”
Section: The Historical Process Of Building What Is Now Known As the mentioning
confidence: 88%
“…In this context, the articles showed that health facilities are made available to cover areas far beyond the capacity of care and once inserted into different realities, return your call followed upright models. 13 Additionally, when the complexity of the cases goes beyond the level of primary care, it is clear that there is no linkage mechanism at this level with more specialized levels of care, which results in poor solutions to meet the demands of health service users. 14 The lack of preventive and promotional health by professionals slips into a curative attention yet, limiting the possibility of a qualified hearing, bond and accountability, which are essential for an effective practice of adherence to therapy.…”
Section: The Historical Process Of Building What Is Now Known As the mentioning
confidence: 99%
See 2 more Smart Citations